Tujuan Pendidikan Islam - Syafe'i, Imam (Universitas Islam Negeri Raden Intan Lampung, 2015)
There are three basic components of human innate. These components are body, spirit, and mind. One is the body, which is developed according to sunatullah means that if humans consume enough food nutrition it will grow like plants and other creatures. While the spirit and the senses evolved to explore themselves through the process of education. The body, the spirit, and the mind is a unity of whole and round and indivisible. According to Jalaluddin the purpose of Islamic education should be formulated from the philosophical value contained in the philosophy of Islamic education. The purpose of Islamic education is identical with the goal of Islam itself. According to Abdurrahman Saleh Abdullah, there are three main objectives of Islamic education, namely that physical objectives (ahdaf al-jismiyyah), spiritual causes (ahdaf a, ruhiyyah-education), and mental objectives (ahdaf al-aqliyyah).